Factors in Digital Marketing Influencing the Decision to Use Outsourced Accounting Services in Bangkok - Jarus, Priyaporn; Sirariyakul, Tassanee (RMUTP Journal of Business and Innovation Management, 2025)
This research aims to (1) examine the general characteristics of organizations that influence their decision to use accounting firm services in Bangkok, and (2) explore the forms of digital marketing that impact such decisions. A quantitative research approach was employed, collecting data from 400 entrepreneurs via an online questionnaire. The sample included members of the BNI network, nationwide contractors, clients of Hi Professional Service accounting firm, and business-owning acquaintances of the researcher. Convenience sampling was used. The questionnaire comprised three sections: screening questions, general organizational information, and questions regarding digital marketing and decision-making related to accounting firm services. Closed-ended questions using a five-point Likert scale were applied. Data analysis involved descriptive statistics (frequency, percentage, mean, and standard deviation) and inferential statistics, including ANOVA and multiple regression analysis, to test the relationship between organizational characteristics, digital marketing forms, and service selection decisions at a significance level of .05. The findings revealed that organizational characteristics such as business type, registration type, registered capital, and duration of operation—significantly influenced the decision to use accounting firm services (Sig. < 0.05). Larger and longer-established businesses were more likely to seek expert services. Regarding digital marketing, content marketing (mean = 4.17), SEO (mean = 4.08), and websites (mean = 3.96) had a statistically significant impact on decision-making, as they enhanced visibility, credibility, and customer reach. The study recommends that accounting firms develop effective digital marketing strategies to improve competitiveness and maintain their customer base.